2015
DOI: 10.1021/acsami.5b08934
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Adhesive Design by Understanding Compliance

Abstract: Adhesives have long been designed around a trade-off between adhesive strength and releasability. Geckos are of interest because they are the largest organisms which are able to climb utilizing adhesive toepads, yet can controllably release from surfaces and perform this action over and over again. Attempting to replicate the hierarchical, nanoscopic features which cover their toepads has been the primary focus of the adhesives field until recently. A new approach based on a scaling relation which states that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…We can calculate the compliance of an adhesive loop closure, by summing the compliance of each individual component of the system . The adhesive loop is composed of three components, a soft elastomer “pad,” a composite “skin,” and a fabric “tendon.” The elastomer pad, of thickness, t e , width, w , length, L e , and modulus, E e , primarily undergoes shear for thin samples tested here, such that Cpad=3tewLeEe …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We can calculate the compliance of an adhesive loop closure, by summing the compliance of each individual component of the system . The adhesive loop is composed of three components, a soft elastomer “pad,” a composite “skin,” and a fabric “tendon.” The elastomer pad, of thickness, t e , width, w , length, L e , and modulus, E e , primarily undergoes shear for thin samples tested here, such that Cpad=3tewLeEe …”
Section: Resultsmentioning
confidence: 99%
“…Here, we show that this scaling parameter also applies when both sides of the interface contribute compliance. Furthermore, we have shown that ( A/C ) 1/2 can be calculated by superposition of the mechanical properties of individual components . An equation was derived specifically to calculate the generalized reversible adhesive scaling parameter for adhesive closures, and again ( A/C ) 1/2 was calculated accurately.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations